Hansemann’s anaplastic theory of cancer after 135 years - Henikoff, Steven; Ahmad, Kami (Frontiers in Epigenetics and Epigenomics, 2025)
Summary: The term “anaplasia” was coined in 1890 to describe chromosomal changes common to primordial cancer cells, but ever since the mechanisms whereby a cell becomes anaplastic has been the subject of much speculation. Recent results based on genomic and epigenomic profiles of cancer patient samples provide a glimpse into early events that lead to aneuploidy, the original defining feature of an anaplastic cell. We propose that the anaplastic cell is one in which RNA Polymerase II hypertranscribes S-phase-dependent histone genes, and the resulting histone excess facilitates DNA replication while competing for CENP-A, causing centromere breaks that initiate whole-arm aneuploidy.